Efektifitas Pemanasan Dinamis Upaya Mengurangi Risiko Cedera Lutut pada Atlet Club Sepak Bola PS Rimbo Ilir - Hidayah, Wisnu; Nugraha, Ugi; Iqroni, David (MAN Insan Cendekia Jambi, 2025)
This study examines the effectiveness of dynamic warm-up exercises as a preventive measure against the risk of knee joint injuries among players at PS Rimbo Ilir football club. Adopting a pre-experimental approach through a single group pretest-posttest design, the research involved 5 subjects with a history of knee trauma. Data collection was implemented using the Y-Balance test protocol which was administered before and after the intervention of a dynamic warm-up program that lasted for 8 weeks with a total of 16 sessions. Data analysis revealed a significant improvement in balance ability, marked by an increase in mean values from 47.9 at initial measurement to 73.4 at final measurement. Statistical testing through paired sample t-test yielded a p-value of 0.000 (p<0.05), confirming the significance of this difference and validating the hypothesis that dynamic warm-up plays an effective role in minimizing the possibility of knee injuries. Based on these findings, researchers recommend the integration of dynamic warm-up as a standard component in training routines to enhance performance and prevent knee injuries among PS Rimbo Ilir athletes.